2017
DOI: 10.1002/jat.3571
|View full text |Cite
|
Sign up to set email alerts
|

Paraquat and MPTP alter microRNA expression profiles, and downregulated expression of miR‐17‐5p contributes to PQ‐induced dopaminergic neurodegeneration

Abstract: Recent evidence indicates that microRNAs (miRNAs) play a key role in neurodegenerative diseases. However, the toxic effects of paraquat (PQ) and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) on miRNA expression profiles in dopaminergic neurons have not been investigated. In the present study, we used microarray analysis to show that PQ and MPTP induce alterations of miRNA expression in neuro-2a cells. The results reveal that treatment with 300 μm PQ caused miRNA deregulation, such that 60 miRNAs were upr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…The misexpression of miR-25 can inhibit proliferation and induce cell apoptosis in AD mouse primary hippocampal cell culture, suggesting miR-17~92 may possess much more complex functions in the pathogenesis of neurodegenerative diseases than previously thought. Furthermore, in an in vitro PD model, the expression levels of miR-17 are significantly reduced, contributing to dopaminergic neurodegeneration and proliferation attenuation [33]. Besides, being a well-recognized primary oncogenic miRNA family, the expression of miR-17~92 is dramatically up-regulated in glioma tissues.…”
Section: Mir-17~92 Family As Pathological Factor In Neurological Disomentioning
confidence: 99%
See 1 more Smart Citation
“…The misexpression of miR-25 can inhibit proliferation and induce cell apoptosis in AD mouse primary hippocampal cell culture, suggesting miR-17~92 may possess much more complex functions in the pathogenesis of neurodegenerative diseases than previously thought. Furthermore, in an in vitro PD model, the expression levels of miR-17 are significantly reduced, contributing to dopaminergic neurodegeneration and proliferation attenuation [33]. Besides, being a well-recognized primary oncogenic miRNA family, the expression of miR-17~92 is dramatically up-regulated in glioma tissues.…”
Section: Mir-17~92 Family As Pathological Factor In Neurological Disomentioning
confidence: 99%
“…Due to its importance in neurogenesis regulation, miR-17~92 family is widely involved in the pathogenesis of neurobiological disorders. For instance, the decay and over-synthesis of miR-17~92 are linked to neurogenesis deficiency in neurodegenerative diseases and uncontrolled cell growth in glioma, respectively [33,34]. Conversely, miR-17~92 family can also be utilized as potential regenerative therapeutics to t r e a t b r a i n i n j u r y v i a s t i m u l a t i n g e n d o g e n o u s neurogenesis [35].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research on the degenerative changes of the nervous system by miRNAs has grown. Wang et al found that PQ‐ and MPTP‐treatment inhibited the expression of miR‐374‐5p ( P < 0.01) in Neuro‐2a cells. Yet, miR‐374‐5p was not associated with several biological processes including regulation of DNA dependent transcription and RNA metabolic processes in the pathogenesis of Parkinson's disease.…”
Section: The Role Of Mir‐374 In Nervous System Diseasementioning
confidence: 99%
“…The miRNAs are also an important epigenetic regulator of gene expression, and the association of abnormal DNA methylation with silencing individual miRNA genes has been found in many cancer types, 26,27 so we would like to investigate the changes in PQ‐induced miRNA expression, whether there is a link between miRNA and DNA methylation. Our pre‐miRNA chip results show that PQ can cause changes in miRNA expression profiles in neuro‐2a cells 3 . qRT‐PCR result verified that PQ downregulated miR‐17‐5p level in neuro‐2a cells (Figure 5).…”
Section: Resultsmentioning
confidence: 52%
“…In our previous study, we found that PQ could cause nerve cell damage and reduce the expression of miR‐17‐5p in neuro‐2a cells. And the downregulated miR‐17‐5p is at least partly involved in PQ‐induced neurotoxicity mechanisms and contributes to proapoptotic effects 3 . What is the way in which PQ induces a decrease in miR‐17‐5p expression and causes neuronal damage?…”
Section: Introductionmentioning
confidence: 99%